2013
DOI: 10.1021/jp4074366
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Adsorption on Gallium Nanoclusters

Abstract: The reactivity of metal nanoclusters can vary significantly as a function of the valence electronic configuration of the cluster. Hydrogen adsorption provides a simple probe to investigate variations in reactivity of nanoclusters and identify factors that contribute to regioselectivity of interactions. In this study density functional theory is used to investigate the structures, stabilities, and electronic properties of doped gallium nanocluster hydrides, Ga 12 XH (X = B, C, Al, Si, P, Ga, Ge, and As). Hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Icosahedral endo-Ga 12 C has been found to be the most stable cluster that exhibits the most jellium-like orbital structure. Moreover, it has been observed that the hydrogen adsorption on these doped clusters is energetically favorable, but adsorption energies vary significantly with valence electron count and the adsorption site . The structures, stabilities, and electronic properties of lithium-doped gallium clusters, Ga n Li ( n = 1–13), have been investigated by means of the B3LYP/LANL2DZ level of theory as well as the dissociation energies, second-order energy differences, and HOMO–LUMO energy gaps .…”
Section: Main Group Metal Clustersmentioning
confidence: 99%
“…Icosahedral endo-Ga 12 C has been found to be the most stable cluster that exhibits the most jellium-like orbital structure. Moreover, it has been observed that the hydrogen adsorption on these doped clusters is energetically favorable, but adsorption energies vary significantly with valence electron count and the adsorption site . The structures, stabilities, and electronic properties of lithium-doped gallium clusters, Ga n Li ( n = 1–13), have been investigated by means of the B3LYP/LANL2DZ level of theory as well as the dissociation energies, second-order energy differences, and HOMO–LUMO energy gaps .…”
Section: Main Group Metal Clustersmentioning
confidence: 99%
“…The RDFT analysis also reveals similarities between the bonding in the Ga atoms of the equatorial region of the endo-Ga 12 X clusters and the ground state of the Ga 2 molecule. The calculated b ε bond indices and surface maps of electronic chemical potential provide understanding for the previously observed regioselectivity for hydrogen atom adsorption [20]. The significant deshielding around the surface atoms, caused by migration of charge towards the core, suggests that these clusters will interact strongly with nucleophiles and Lewis bases.…”
Section: Discussionmentioning
confidence: 80%
“…However, as shown previously [19] the Ga 2 subunits and axial bonds of these clusters are particularly sensitive to changes in the bonding environment within the cluster. In our recent study [20] we probed the reactivity of doped gallium nanoclusters and identified distinct regioselectivity for hydrogen adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Figures 2h,i shows how the resonances blueshift and damp in agreement with the experimental results (Figure 2e,f,h,i), as the electron density in the particle increases, because of the donor character of hydrogen (see Section S1, Supporting Information for details). This indicates that the electron density in the Ga NPs increases [ 36 ] consistently with the electron donor character of interstitial hydrogen, [ 37 ] as well as with the formation of metallic GaH 5 and/or GaH 3 phases. The liquid Ga accommodates reversible plastic distortion and the hydrogenation process maintains the metallic character of the NP.…”
Section: Resultsmentioning
confidence: 99%